Sunrise Presentations: A study in valuing and divesting a small business - Cyndi Barrus; James C. Brau; Amy Cyr; Jessica West (The Journal of Entrepreneurial Finance (JEF), 2018)
Sarah Barnett has decided to go back to school to earn an MBA. For several years she has run a graphic design business. Sarah has unexpectedly been accepted into the MBA program with a scholarship a year earlier than she planned. Classes begin in two weeks and the school she is attending does not allow first year MBAs to work outside of the school curriculum. Sarah has decided to divest her business and now must consider several options to do so. She is most concerned about making sure her customers continue to receive outstanding service, and secondarily concerned about selling the business for enough to pay off the business debt and to help pay her living expenses while she is a graduate student.
Keywords: 650